2021
DOI: 10.2147/cmar.s300738
|View full text |Cite
|
Sign up to set email alerts
|

Low Expression of Circular RNA hsa_circ_0078607 Predicts Poor Prognosis in High-Grade Serous Ovarian Cancer

Abstract: Objective: Recent studies have shown that circRNAs participate in ovarian cancer progression and act as potential biomarkers for ovarian cancer diagnosis and prognosis. In the present study, we aimed to investigate the expression pattern and prognostic significance of circ_0078607 in high-grade serous ovarian cancer (HGSOC). Methods: The expression of circ_0078607 was detected by quantitative real-time polymerase chain reaction (qRT-PCR) in 49 cases of HGSOC. Clinical data of patients with HGSOC were retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…M 6 A plays an important role in numerous biological processes, which contributes to cancer development, cancer cell proliferation and cancer stem cell self-renewal ( 28 , 29 ). The expression profile and potential function of circRNAs in different cancers have been identified, including HGSOC ( 13 , 30 , 31 ). As a new epitranscriptomic marker, m 6 A is recognized as a reversible and dynamic RNA modification in eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…M 6 A plays an important role in numerous biological processes, which contributes to cancer development, cancer cell proliferation and cancer stem cell self-renewal ( 28 , 29 ). The expression profile and potential function of circRNAs in different cancers have been identified, including HGSOC ( 13 , 30 , 31 ). As a new epitranscriptomic marker, m 6 A is recognized as a reversible and dynamic RNA modification in eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Circ_0078607 has been found to repress tumor progression via modulating the miR-518a-5p and Fas signaling pathway in ovarian cancer ( Zhang et al, 2020c ). Moreover, circ_0078607 expression was lower in high-grade serous ovarian cancer and associated with poor prognosis ( Zhang et al, 2021d ). Furthermore, circ_0078607 was reported to inhibit tumor progression via governing the miR-32-5p and SIK1 pathways in ovarian cancer ( Jin and Wang, 2022 ).…”
Section: Role Of Circrnas In Drug Resistancementioning
confidence: 99%
“…Moreover, circ_0078607 levels were reported to be decreased in HGSC tissues and were negatively correlated with the FIGO stage and serum CA125 levels. The subsequent Cox regression analysis showed that reduced circ_0078607 level was a risk factor for poor PFS and OS [ 109 ]. These findings suggest that high levels of circEXOC6B, circN4BP2L2, circITCH, and circ_0078607 are good prognostic markers for EOC patients.…”
Section: Circrnas As Potential Biomarkers In Eocmentioning
confidence: 99%